Cord‐blood respiratory syncytial virus antibodies and respiratory health in first 5 years of life. Issue 12 (29th September 2021) - Takashima, Mari D.; Grimwood, Keith; Sly, Peter D.; Lambert, Stephen B.; Chappell, Keith J.; Watterson, Daniel; Young, Paul; Kusel, Merci; Holt, Barbara; Holt, Patrick; Ware, Robert S.
Abstract: Objective: To determine the potential longer‐term effects of maternal antenatal respiratory syncytial virus (RSV) vaccination, we examined the association between cord‐blood RSV‐neutralizing antibodies (RSV‐NA) and RSV infections in the first 2 years of life, RSV‐NA at 3 years, and respiratory health to age 5 years. Methods: Two community‐based Australian birth cohorts were combined. For children with at least one atopic parent, paired serum RSV‐NA levels were compared in cord blood and at age 3 years. Weekly nasal swabs were collected in one cohort and during acute respiratory infections (ARI) in the other. Wheeze history up to age 5 years and physician‐diagnosed asthma at 5 years was collected by parent report. Results: In 264 children, each log10 increase of cord‐blood RSV‐NA level was associated with 37% decreased risk (adjusted incidence‐rate‐ratio [aIRR] 0.63; 95% confidence interval [CI]: 0.40–1.01) of RSV‐ARI and 49% decreased risk (aIRR 0.51; 95% CI: 0.25–1.02) of RSV acute lower respiratory infections (ALRI) at 12–24 months of age. However, higher cord‐blood RSV‐NA was associated with increased risk of all‐cause ALRI (aIRR 1.29; 95% CI: 0.99–1.69), wheeze‐associated ALRI (aIRR 1.75; 95% CI: 1.08–2.82), and severe ALRI (aIRR 2.76; 95% CI: 1.63–4.70) at age 6–<12 months. Cord‐blood RSV‐NA was not associated with RSV‐ARI in the first 6‐months, RSV‐NA levels at 3 years, or wheeze or asthma at 5 years. Conclusions: Higher levels of cord‐blood RSV‐NA did not protect against RSV infections during the first 6‐months‐of‐life, time‐to‐first RSV‐ARI, or wheeze or asthma in the first 5 years of life. Additional strategies to control RSV‐related illness in childhood are needed.